Calculate the Estimated Tanker Berthing Time Based on the Amount of Ethylene Loaded - Yudhiyono, Yudhiyono; M. Yusuf, M. Yusuf; sugiyanto, sugiyanto (Meteor STIP Marunda, 2023)
Ethylene is a cryogenic liquefied gas cargo transported at approximately −104°C, requiring specialized handling procedures that significantly influence tanker berthing duration at loading terminals. Accurate estimation of berthing time is essential for terminal scheduling, berth utilization optimization, and operational cost management. This study aims to calculate the estimated tanker berthing time based on the amount of ethylene loaded by developing a predictive regression model. Data were collected from 20 ethylene carrier calls at a petrochemical terminal over a two-year period (2022–2023), comprising records of cargo volume (Metric Tons), loading rate (MT/hour), cool-down time, and total berthing time extracted from Statement of Facts (SoF) documents. A multiple linear regression analysis was performed with berthing time (Y) as the dependent variable and cargo volume (X₁) and loading rate (X₂) as independent variables. The results show that cargo volume and loading rate jointly explain 94.7% of the variance in berthing time (R² = 0.947, Adjusted R² = 0.941). The regression model Y = 5.832 + 0.00384X₁ − 0.0267X₂ indicates that each additional Metric Ton of ethylene increases berthing time by approximately 0.23 minutes, while higher loading rates reduce berthing time. The F-test confirms model significance (F = 152.34, p < 0.001), and both independent variables are individually significant (p < 0.05). The model provides a practical tool for terminal planners and ship agents to estimate berthing duration and improve berth allocation efficiency.